Fashions Between Form & Content In Shows of School Drama: محمود جباري حافظ -خــــــالد عبـــــاس شـــــايع (Al-Academy, 2020)
Shows of school drama are consisted of visual elements ( Actor (Student ) , ( Fashions , Decoration , Lighting , Make Up , Accessories ) for these elements have privacy being penetrate inside education institutions ( School ) , besides to property of thought direction , teaching for school drama generally , from among these elements are fashions with their designs , colors and various shapes which address student directly by visual . They affect on him as form or content pursuant to movements or design tackles which are made under directive settings and aims of school drama show wholly . Accordingly , this current study presented question for problem of research . Which it is what is relation between form and content for drama fashions to access educational thoughts to the watcher ( Student ) ? . Whereas the target beyond that is ( Detection for visual relation for form of fashions with its hidden thoughtful implications within shows of school drama ) , but researches were as following : Firstly ( Historical settings for fashions over shows of school drama ) , secondly ( Design relation for form , content for fashions in school drama ) , however proceeds of research were course of research (Analytical descriptive ) . The most important of results of research : Diversity forms of fashions of figures ( As human race or animal or plant ) bear certain content , narrowness in articulation for movements of those bodily figures, but did not bear their national actions and the research was concluded by references